MACEDONIAN STUDENTS’ ATTITUDES TO ENGLISH: A COMPARATIVE PERSPECTIVE ACROSS REGIONS (PALIMPSEST / ПАЛИМПСЕСТ, 2025)
This study explores Macedonian students’ attitudes to English across three contexts: Skopje, other urban centres, and rural communities. Data were gathered through a questionnaire designed to elicit students’ perceptions of the benefits and drawbacks of English in their everyday lives. Responses were subjected to a thematic coding analysis, and combined qualitative insights with quantitative frequency counts. Five broad themes were identified: knowledge and cognitive development, communication and social connectivity, mobility and practical advantages, access to information and opportunities, and identity and language preservation. English was overwhelmingly perceived as a valuable resource, with identity and language preservation and communication and social connectivity being the predominant themes across the three contexts. Regional variation revealed subtle differences: students from rural areas valued communication and social connectivity most, students from Skopje areas were most concerned about identity and language preservation issues, while students from other towns balanced both of these concepts. These findings underscore the dual role of English, both as a gateway to global developments and as a perceived threat to local identity, pointing to the need for language policies that foster both English proficiency and Macedonian language maintenance.
Keywords: attitudes to English; Macedonian students; thematic analysis; sociolinguistic variation; language preservation.